Nanostructured high-entropy materials. Issue 8 (28th April 2020) - Haché, Michel J.R.; Cheng, Changjun; Zou, Yu
Abstract: Abstract : In the past decade, the emergence of high-entropy alloys (HEAs) and other high-entropy materials (HEMs) has brought about new opportunities in the development of novel materials for high-performance applications. In combining solid-solution (SS) strengthening with grain-boundary strengthening, new material systems—nanostructured or nanocrystalline (NC) HEAs or HEMs—have been developed, showing superior combined mechanical and functional properties compared with conventional alloys, HEAs, and NC metals. This article reviews the processing methods, materials, mechanical properties, thermal stability, and functional properties of various nanostructured HEMs, particularly NC HEAs. With such new nanostructures and alloy compositions, many interesting phenomena and properties of such NC HEAs have been unveiled, for example, extraordinary microstructural and mechanical thermal stability. As more HEAs or HEMs are being developed, a new avenue of research is to be exploited. The article concludes with perspectives about future directions in this field.